Lot-to-lot stability of antibody reagents for flow cytometry - Böttcher, Sebastian; van der Velden, Vincent H J; Villamor, Neus; Ritgen, Matthias; Flores-Montero, Juan; Escobar, Hugo Murua; Kalina, Tomas; Brüggemann, Monika; Grigore, Georgiana; Martin-Ayuso, Marta; Lecrevisse, Quentin; Pedreira, Carlos E; et al. (Journal of immunological methods, 2019)
The fluorescence detected using fluorochrome-labelled monoclonal antibodies depends not only on the abundance of the target antigen, but amongst many other factors also on the effective fluorochrome-to-antibody ratio. The diagnostic approach of the EuroFlow consortium relies on reproducible fluorescence intensities over time. A capture bead system for mouse immunoglobulin light chains was utilized to compare the mean fluorescence intensity of 1323 consecutive antibody lots to the currently used lot of the same monoclonal antibody. In total, 157 different monoclonal antibodies were assessed over seven years. Median relative difference between consecutive lots was 3.8% (range: 0.01% to 164.7%, interquartile range: 1.3% to 10.1%). The relative difference exceeded 20% in 8.8% of all comparisons. FITC labelled monoclonal antibodies (median relative difference: 2.1%) showed a significantly smaller variation between lots than antibodies conjugated to PE (3.5%), PECy7 (3.9%), PerCPCy5.5 (5.8%), APC (5.8%), APCH7 (7.4%), and APCC750 (14.5%). Reagents labelled with Pacific Blue (1.4%), Pacific Orange (2.4%), HV450 (0.7%), and HV500 (1.7%) demonstrated more consistent results compared to conjugates of BV421 (4.1%) and BV510 (16.2%). Additionally, significant differences in lot-to-lot fluorescence stability amongst antibodies labelled with the same fluorochrome were observed between manufacturers. These observations might guide future quality recommendations for the production and application of fluorescence-labelled monoclonal antibodies in multicolor flow cytometry.
Keywords: reprodukovatelnost výsledků; Mice; monoklonální protilátky; Fluorescence intensity; Antibodies, Monoclonal; průtoková cytometrie; Animals; fluorescenční barviva; Flow cytometry; Variability; Fluorescent Dyes; Protein Stability; Flow Cytometry; Reproducibility of Results; zvířata; myši; Fluorochrome-to-antibody ratio; stabilita proteinů